Metodologi Ekonomi Islam: Suatu Analisis Perbandingan - Borhan, Joni Tamkin (Jurnal Usuluddin, 2002)
The methodology of Economics discussed by the economists covers the topics of positive vs. normative, inductive vs. deductive, incorporation vs. exclusion of values, prescription vs. description, apriorism vs. empiricism, etc. This article discusses in broad terms the methodology of Islamic Economic and to show its differences from the methodology of conventional economics. It also discusses some of the methodological issues relating to Islamic economics such as Islamic economics as a positive and normative sciences and the differences between Islamic economics and fiqh muamalah.